Knowledge driven development : Private extension and global lessons - Yuan, Zhou; Babu, Suresh Chandra (London Academic Press, 2015)
This book examines private extension models in agricultural value chains, emphasizing knowledge sharing, capacity building, and diverse approaches to service delivery. Drawing on ten case studies, it analyzes the context, efficiency, sustainability, and impact of private extension, and compares it with public systems. The volume highlights trends, commonalities, and lessons for replication and scaling up, offering recommendations for future agricultural development policies and programs worldwide.
Includes index
Keywords: Kinh tế chính trị